2011
DOI: 10.1155/2011/340869
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Intestinal Erosions as a Result of Hemorrhage due to Parasites: Case Reports and Review of the Literature

Abstract: Obscure gastrointestinal bleeding appears to be uncommon in patients with parasites. In spite of that some reports had described this relationship in patients evaluated during capsule endoscopy procedures; the characteristic of the bleeding lesions remains unclear. This paper describes two patients with a massive obscure gastrointestinal bleeding due to ascariasis, using the new capsule endoscopy technology “MiroCam”, describing the characteristic of the lesions found in our patients (observed in a better imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…On the other hand, ascariasis manifesting as bowel perforation and gastrointestinal bleeding is uncommon. There are few reported cases of ascariasis that manifest gastrointestinal intraluminal bleeding; this is mostly seen in pediatric patients ( 3 4 5 6 ), and worms are uncommonly found in the mesentery or mesocolon. Jeong et al ( 7 ) reported a case of omental involvement of Paragonimus westermani with conglomerated calcifications in pelvic cavity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ascariasis manifesting as bowel perforation and gastrointestinal bleeding is uncommon. There are few reported cases of ascariasis that manifest gastrointestinal intraluminal bleeding; this is mostly seen in pediatric patients ( 3 4 5 6 ), and worms are uncommonly found in the mesentery or mesocolon. Jeong et al ( 7 ) reported a case of omental involvement of Paragonimus westermani with conglomerated calcifications in pelvic cavity.…”
Section: Discussionmentioning
confidence: 99%
“…"una causa no sospechada" R.F.S Revista Facultad de Salud Julio-Diciembre de 2015;7(2):57-60 hemorragia digestiva de origen oscuro oculta o manifiesta, siendo la presentación con anemia ferropenica y sangre oculta en heces la más frecuente, e inusualmente con sangrado evidente, donde se ha requerido la realización de varios procedimientos endoscópicos para llegar al diagnóstico [16][17][18][19][20][21][22] . Lo que plantea el interrogante si a estos pacientes que se presentan por primera vez con sangrado gastrointestinal y evaluación endoscópica estándar negativa deben ser desparasitados profilácticamente en zonas donde la prevalencia de parasitismo intestinal es alta, como nuestro país, antes de presentar un nuevo episodio de sangrado y requerir la realización de más procedimientos endoscópicos para determinar la etiología, como ocurrió en nuestra paciente.…”
Section: Discussionunclassified